Uncommon cause of fever in a child with steroid-dependent nephrotic syndrome - Sethi, Sidharth Kumar (Clin Nephrol Case Stud, 2020)
Background: Children with nephrotic syndrome are vulnerable to developing infections due to a state of relative immunodeficiency, malnourishment, and use of immunosuppression. Case characteristics: We herein report the case of a 3-year-old child with steroid-dependent nephrotic syndrome who presented to us with fever of unknown origin. Observation: The child was found to have an atypical mixed infection with mycoplasma and cytomegalovirus. Outcome: The infection completely resolved with appropriate treatment and lowering of immunosuppression. Message: Persistently febrile pediatric patients, especially in the setting of recent immunosuppression and absence of otherwise-identified infectious pathogens, should be screened for atypical mixed infections.